Optimum Shape Design of Metal-Enclosed 550 kV Disconnectors Based on Response Surface Method and Finite Element Analysis - Gong, R.; Wang, S.; Luo, X.; Danikas, M. (Engineering, Technology & Applied Science Research, 2015)
In this paper, the optimum shape design of 550 kV disconnectors in Gas Insulated Switchgears (GIS) are firstly presented employing the Finite Element Method (FEM) for electric field analysis coupled with an optimal design method. For effective analysis, the FEM is conducted in transient quasistatic electric field, using a finite element FORTRAN code. The structure parameters of disconnectors that provide the required electric field strength are obtained by the Response Surface Method (RSM) and the optimal values are presented by the variation in maximal electric field strength. The RSM and optimal design methods are also conducted by FORTRAN codes. The optimal result reveals that a uniform electric field distribution is achieved in 550 kV disconnectors. Additionally, the optimal result of disconnectors is verified by the proposed disconnector undertaken power frequency withstanding voltage of 740 kV for 1 minute, lightening impulse of 1675 kV, and operating impulse of 1300 kV, respectively.